2018
DOI: 10.1097/md.0000000000013450
|View full text |Cite
|
Sign up to set email alerts
|

Serum cytokine profiles and Mac-2 binding protein glycosylation isomer (M2BPGi) level in patients with autoimmune hepatitis

Abstract: Autoimmune hepatitis (AIH) is an autoimmune liver disease that is characterized by a progressive destruction of the liver parenchyma and the development of liver fibrosis. We aimed to examine the relationship between circulating cytokines/chemokines and the Mac-2 binding protein glycosylation isomer (M2BPGi) levels in Japanese patients with autoimmune hepatitis (AIH).We investigated the relationship between circulating cytokines/chemokines and M2BPGi levels in Japanese patients with AIH. Seventy-seven patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…A novel serum fibrosis marker, i.e., Mac-2 binding protein glycosylation isomer (M2BPGi), which was originally reported to be associated with the fibrosis stage in CHC patients [ 24 ], is likely to become an alternative to the use of VCTE; the M2BPGi value is influenced by both inflammation and fibrosis in AIH patients, in a similar way to VCTE [ 25 ]. A ‘one-serum parameter fits all’ approach to the evaluations of disease activity and fibrosis could be achievable with serum M2BPGi, but further studies are necessary to validate its utility.…”
Section: Diagnosismentioning
confidence: 99%
“…A novel serum fibrosis marker, i.e., Mac-2 binding protein glycosylation isomer (M2BPGi), which was originally reported to be associated with the fibrosis stage in CHC patients [ 24 ], is likely to become an alternative to the use of VCTE; the M2BPGi value is influenced by both inflammation and fibrosis in AIH patients, in a similar way to VCTE [ 25 ]. A ‘one-serum parameter fits all’ approach to the evaluations of disease activity and fibrosis could be achievable with serum M2BPGi, but further studies are necessary to validate its utility.…”
Section: Diagnosismentioning
confidence: 99%
“…Although close monitoring of fibrosis staging is essential during the clinical course, it is not feasible to carry out serial liver biopsies, and the role of noninvasive indices for fibrosis staging has been paid more attention to recently. These indices include biochemical calculation scores, such as the aspartate aminotransferase/platelet ratio (APRI) or fibrosis index based on the 4 factors (FIB-4), 24 Mac-2 binding protein glycosylation isomer, 25 magnetic resonance elastography, 26 and transient elastography. 27,28 A recent systematic review indicated that transient elastography had a good performance for determining significant fibrosis, advanced fibrosis, and cirrhosis, whereas APRI and FIB-4 showed poor performance.…”
Section: Presentationmentioning
confidence: 99%
“… 36 37 In addition, RAAS inhibitors are protective effectors for diabetic retinopathy. 38 Furthermore, intercellular adhesion molecule-1 is associated with liver fibrosis, 39 and diabetic microangiopathy 40 and macroangiopathy. 41 Thus, M2BPGi, which is a surrogate marker of liver fibrosis, has a close association with diabetic microangiopathy and macroangiopathy.…”
Section: Discussionmentioning
confidence: 99%